Analisis Stabilitas Bangunan Pengaman Pantai (Revetment) di Pantai Muli Lampung Selatan - Tomi, Muhammad; Zakaria, Ahmad; Tugiono, Subuh; Kusumastuti, Dyah Indriana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
This study analyzes the revetment structure located at Muli Beach, South Lampung, through wave analysis occurring at the beach. The stability of the coastal protection structure, revetment, at Muli Beach is of utmost importance due to safety and security concerns for beach users. If the revetment is unstable, it can cause damage to the structure and potentially pose hazards to the users. The aim of this research is to assess the stability of the revetment structure against high waves occurring at the beach. The analysis method employed in this study utilizes wave forecasting with a return period of 10 years. The analysis also encompasses the examination of the components constituting the revetment structure at Muli Beach. The research findings indicate that the composition of the revetment structure is unstable against high waves. The wave forecasting analysis at Muli Beach resulted in a significant wave height, Hs = 1,02 m and a wave height at breaking point Hb = 1,82 m. Regarding the structure's components, there are several shattered stones > 2, indicating inconsistency with the existing literature. In the analysis of the revetment toe protection, a stability coefficient value of Ns^3 = 290 was obtained, which can be considered safe. Based on these analysis results, it is recommended to implement necessary measures to prevent the collapse of the revetment structure during high wave events. Keywords: revetment, waves, stability, beach.